2013
DOI: 10.1111/j.1365-4632.2012.05751.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematological study of patients with aphthous stomatitis

Abstract: There is still no conclusive evidence relevant to the etiopathogenesis of RAS. Routine hematological screening and tests for serum iron, folic acid, and vitamin B12 deficiencies should be assessed in all patients with RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 16 publications
2
30
2
3
Order By: Relevance
“…Lopez-Jornet et al 15 found a higher overall frequency (14.14%) of HD in the RAS group versus the control group (6.39%), but the difference was not statistically significant. Koybasi et al 4 only found an association between vitamin B12 levels and RAS history.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Lopez-Jornet et al 15 found a higher overall frequency (14.14%) of HD in the RAS group versus the control group (6.39%), but the difference was not statistically significant. Koybasi et al 4 only found an association between vitamin B12 levels and RAS history.…”
Section: Discussionmentioning
confidence: 88%
“…16 Numerous studies have reported a high incidence (4-56, 2%) of HD in patients with RAS. 5,8,11,[15][16][17][18] Iron, vitamin B12 and folic acid deficiencies were reported as predisposing factors in RAS in several studies. 4,5,8,10,11,16,18 Porter et al 18 have determined the frequency of anaemia and/or HD in RAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in several studies, researchers have indicated that deficiencies in vitamins, such as folic acid, B1, B2, and B6, are involved in the recurrence of pathogenesis (4). It was also revealed that 28% of patients with recurrence had a deficiency in one or more vitamins B group (3)(4)(5)(6)(7)(8). Vitamin B group is a group of water-soluble vitamins playing an important role in the cell metabolism process.…”
Section: Introductionmentioning
confidence: 99%
“…1) In addition, oral ulcer is associated with a variety of underlying systemic diseases, including chronic inflammatory bowel diseases, gluten enteropathy, agranulocytosis, and cyclical neutropenia.…”
mentioning
confidence: 99%